Potassium deficiency inhibits steviol glycosides synthesis by limiting leaf sugar metabolism in stevia (Stevia rebaudiana Bertoni) plants - Yu-ming SUN; Xiao-lei HUANG; Ting ZHANG; Yong-heng YANG; Xiao-fang CHENG; Xiao-yang XU; Hai-yan YUAN (Journal of Integrative Agriculture, 2021)
The steviol glycosides (SGs) in stevia (Stevia rebaudiana Bertoni) leaves are becoming increasingly valuable due to its high sweetness but low calorific value, which is driving the development of stevia commercial cultivation. Optimizing fertilization management can effectively increase SGs productivity, but knowledge on the relationship between potassium (K) fertilization and SGs production is still lacking. In this study, pot experiments were conducted in order to investigate the effect of K deficiency on SGs synthesis in stevia leaves, as well as the underlying mechanisms. Our results showed that when compared with standard K fertilization, K deficiency treatment has no significant effect on the biomass of stevia plant grown in a given soil with high K contents. However, K deficiency critically decreased leaf SGs contents as well as the expression of SGs synthesis-related genes. The contents of different sugar components decreased and the activities of sugar metabolism-related enzymes were inhibited under the K deficiency condition. Moreover, spraying sucrose on the leaves of stevia seedlings diminished the inhibitory effect caused by K deficiency. Our results also revealed the significant positive correlations between sucrose, glucose and SGs contents. Overall, our results suggest that K deficiency would suppress the synthesis of SGs in stevia leaves, and this effect may be mediated by the leaf sugar metabolism. Our findings provide new insights into the improvement of SGs production potential.